Genotype-Phenotype and Genotype-Origin Correlations in Children with Mediterranean Fever in Germany – an AID-Net Study - Jeske, M.; Lohse, P.; Kallinich, T.; Berger, T.; Rietschel, C.; Holzinger, D.; Kamlah, C.; Lankisch, P.; Berendes, R.; Dueckers, G.; Horneff, G.; Lilienthal, E.; Haas, J. P.; Giese, A.; Dressler, F.; Berrang, J.; Braunewell, L.; Neudorf, U.; Niehues, T.; Föll, D.; Lainka, E. (Klinische Pädiatrie, 2013)
Familial Mediterranean fever (FMF) is the most inherited common autoinflammatory disease (AID) with mutations in the MEFV (MEditerraneanFeVer) gene.The Mor- and Pras-Score modified for children and C-reactive protein (CRP) were used to assess FMF disease severity in Germany. We evaluate the applicability of the 2 severity scores and the correlations between ethnic origin, phenotype, and genotype.Among 242 children (median 5 age at diagnosis), we detected 431 pyrin mutations and 22 different sequence variants, including one new mutation (p.Gly488Asp). The 5 most frequent alterations were p.Met694Val (55.2%), p.Met680lle (11.8%), p.Val726Ala (10%), p.Glu148Gln (7.9%) and p.Met694IIe (2.3%). The prevailing ancestries of 223 cases were Turkish (82.5%) and Lebanese (8.1%). Homozygous p.Met694Val substitution (30.2%) was associated with a more severe disease activity by Mor-Score, as well as with a higher mean CRP (74 mg/l) compared to patients with other mutations. Indeed, Mor- and Pras-Score were inconsistent with each other. A typical distribution of mutations in different ethnic populations was obvious, but not statistically verifiable due to the low number of cases.The homozygous p.Met694Val substitution was associated with a more severe disease activity in our German cohort. The common severity scores were inconsistent in children.
Keywords: FMF; AID; MEFV gene; pyrin; phenotype; HRF